2010
DOI: 10.1007/s12079-010-0087-x
|View full text |Cite
|
Sign up to set email alerts
|

CCN5, a secreted protein, localizes to the nucleus

Abstract: CCN5, a member of the CCN family of growth factors, inhibits the proliferation and migration of smooth muscle cells in cell culture and animal models. Expressed in both embryonic and adult tissues, CCN5 exhibits a matricellular localization pattern characteristic of secreted proteins that are closely associated with the cell surface. In addition to this observed expression pattern, immunohistochemical evidence suggests the presence of nuclear CCN5 in some cells. To determine if CCN5 localizes to the nucleus we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Furthermore, it has also been reported that CCN6/WISP-3 can localize to the nuclei of breast cancer cells (22). Finally, it has been reported that CCN2 and CCN5 are detected in the cytoplasmic compartment as well as the nuclear compartment in many rodent embryonic and adult tissues as well as in fetal human tissues (20,27,50). Collectively, these data are suggestive of diverse functions for the CCN family, including nuclear function for several of its members.…”
mentioning
confidence: 86%
“…Furthermore, it has also been reported that CCN6/WISP-3 can localize to the nuclei of breast cancer cells (22). Finally, it has been reported that CCN2 and CCN5 are detected in the cytoplasmic compartment as well as the nuclear compartment in many rodent embryonic and adult tissues as well as in fetal human tissues (20,27,50). Collectively, these data are suggestive of diverse functions for the CCN family, including nuclear function for several of its members.…”
mentioning
confidence: 86%
“…In a secretome analysis of human SAT, comparing lean and obese patients, WISP2 came out as a top candidate being upregulated in obesity (66). WISP2 is most highly expressed in SAT, primarily in MSCs, fibroblasts, and preadipocytes, and acts both intra-and extracellularly (87,313). In addition, our laboratory has found that secreted WISP2 has the potential to enhance the proliferation of MSCs in both white (WAT) and brown adipose tissue (BAT) (88).…”
Section: Wisp2 a Secreted Wnt-associatedmentioning
confidence: 99%
“…Given the capacity of matricellular proteins to bind other ECM components, their putative roles as chaperones for these molecules and perhaps growth factors are reasonable ( Chlenski et al, 2004 ; Emerson et al, 2006 ). Some matricellular proteins have also been identified in nuclear compartments (SPARC, CCN5, amino-domain truncated CCN3) ( Gooden et al, 1999 ; Planque et al, 2006 ; Wiesman et al, 2010 ), although the nuclear roles of matricellular proteins remain unclear. Nonetheless, the possibility that matricellular proteins act as intracellular targeting or transport molecules warrants further investigation.…”
Section: Members Of the Matricellular Familymentioning
confidence: 99%